Evaluation of later morphologic alterations in renal artery wall and renal nerves in response to catheter-based renal denervation in sheep: comparison of the single-point and multiple-point ablation catheters - Táborský, M; Richter, D; Tonar, Z; Kubíková, T; Herman, A; Peregrin, J; Husková, Z; Kopkan, L (Physiological research, 2018)
This study evaluated the subacute morphologic alterations in renal artery wall and renal nerves in response to catheter-based renal denervation (RDN) in sheep and also compared the efficiency of single-point and multiple-point ablation catheters. Effect of each ablation catheter approved for the clinical use (Symplicity Flex(TM), Medtronic, Inc., or EnligHTN(TM), St. Jude Medical, INC.) was compared to intact contralateral renal artery in 12 sheep by histopathology and immunohistochemistry evaluation after a 10-day period post-RDN procedure. The safety was verified by extensive evaluation of kidney morphology. Vascular wall lesions and nerve injuries were more pronounced in those animals treated with multi-point EnligHTN catheter when compared with animals treated with single-point Symplicity Flex catheter. However, neither RDN procedure led to complete renal nerve ablation. Both systems, tested in the present study, provided only incomplete renal nerve ablation in sheep. Moreover, no appreciable progression of the nerve disintegration in subacute phase post-RDN procedure was observed. This study further supports the notion that the effectiveness remains fully dependent on anatomical inter-individual variability of the sympathetic nerve plexus accompanying the renal artery. Therefore, new systems providing deeper penetrance to targeted perivascular structure would be more efficient.
Keywords: Renal Artery; ledviny; náhodné rozdělení; zvířata; Sheep; sympatektomie; mužské pohlaví; Catheters; Random Allocation; katetrizační ablace; ovce; arteria renalis; Sympathectomy; ženské pohlaví; Catheter Ablation; Animals; Kidney; katétry; Male; Female